Resisting moralisation in health promotion - Brown, R (Springer Verlag, 2018)
Health promotion efforts are commonly directed towards encouraging people to discard ‘unhealthy’ and adopt ‘healthy’ behaviours in order to tackle chronic disease. Typical targets for behaviour change interventions include diet, physical activity, smoking and alcohol consumption, sometimes described as ‘lifestyle behaviours.’ In this paper, I discuss how efforts to raise awareness of the impact of lifestyles on health, in seeking to communicate the (perceived) need for people to change their behaviour, can contribute to a climate of ‘healthism’ and promote the moralisation of people’s lifestyles. I begin by summarising recent trends in health promotion and introducing the notion of healthism, as described by Robert Crawford in the 1980s. One aspect of healthism is moralisation, which I outline (alongside the related term moralism) and suggest is facilitated by efforts to promote health via information provision and educational strategies. I propose that perceived responsibility plays a role in mediating the tendency to moralise about health and behaviour. Since I argue that states ought to avoid direct and indirect moralisation of people’s health-related behaviour, this suggests states must be cautious with regards to the use of responsibility-indicating interventions (including informational and educational campaigns) to promote health.